CoMo-nity challenge: Inducing flow to stimulate controllership team creativity - Gaspar, Rey Mark Intong (Animo Repository, 2023)
According to Csikszentmihalyi (1990), no one is genetically predisposed to disadvantage. Hence, anybody can experience flow at some point in their lives. Learning accelerates when a person is "in the zone" or in a flow state. One goal of this action research is to induce a flow environment that encourages the creativity of the controllership team members. At the same time, their skills are being tested through different levels of challenges. Csikszentmihalyi (2008) says that flow is a state of happy energy free of negative thoughts and feelings, while Su et al. (2014) describe thriving as the state of positive functioning at its fullest potential—mentally, physically, and socially. Thus, this paper made a bold attempt to understand the controllership team members' skills, and improve their skill levels and well-being, while testing how well Csikszentmihalyi (2008) flow theory works in the real world and tracking the team members' well-being through the use of Su et al. (2014) Comprehensive Inventory of Thriving. Throughout the intervention, we have challenged the Controllership team members to partake in the weekly activities that would help them acquire the right knowledge on cutting-edge technology such as Power BI, KNIME, SharePoint, etc., and build their capabilities and expertise in modernizing and automating their processes. Challenges were diligently matched to the team members' skills. The level of the challenges increases as the team members' skills improve. This is based on Csikszentmihalyi's (2008) assertion that flow can only be seen when there is a good balance between the challenges at hand and the person's ability and skills; otherwise, anxiety, lack of interest or even low morale will result.